Lexicology of potters in Podujevo - Jašović, Golub M. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
This paper deals with the lexicology of potters in Podujevo. Materials have been recorded from the interview with a Serbian resident from Podujevo. Revisions and supplementations of the recorded materials have been conducted in 2003rd, in Trstenik, where Nedeljko, a potter, lived with his family. After living Podujevo he retired and quitted making pottery.A list of pottery names have also been done, as well as the Dictionary of the examined lexemes.  Each entry was defined, grammatical and accentually. Semantic and lexical analyses of pottery terms have also been done.